Digital PCR outperforms quantitative real-time PCR for the detection and quantification of major periodontal pathobionts - Haris Munjaković; Katja Povšič; Mario Poljak; Katja Seme; Rok Gašperšič; Lucijan Skubic (Journal of Oral Microbiology)
Background This study comparatively evaluated the analytical and diagnostic performance of a multiplex digital polymerase-chain reaction (dPCR) assay and a quantitative real-time PCR (qPCR) for the simultaneous detection and quantification of periodontal pathobionts: Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum.Materials and Methods Subgingival plaque samples from 20 periodontitis patients and 20 periodontally healthy controls were analyzed. Several analytical parameters of the dPCR assay, optimized using DNA standards, were assessed versus qPCR: dynamic range linearity, precision, accuracy, prevalence, sensitivity, specificity, and concordance. The statistical analyses included Mann-Whitney U test, Wilcoxon test, McNemar’s test, and Bland-Altman plots.Results dPCR showed high linearity (R2 > 0.99) and lower intra-assay variability (median CV%: 4.5%) than qPCR (p = 0.020), with comparable accuracy and agreement. dPCR demonstrated superior sensitivity, detecting lower bacterial loads, particularly for P. gingivalis and A. actinomycetemcomitans. The Bland-Altman plots highlighted good agreement at medium/high loads but discrepancies at low concentrations (< 3 log10Geq/mL), resulting in qPCR false negatives and a 5-fold underestimation of the prevalence of A. actinomycetemcomitans in periodontitis patients. High concordance between the assays was observed for F. nucleatum across both study groups.Conclusions dPCR outperformed qPCR for quantifying periodontal pathobionts and had superior sensitivity and precision, making it particularly effective in detecting low-level bacterial loads.